Role of large transverse fasciocutaneous cross leg flap (whole leg flap) in lower extremity salvage - Zade, Manish; Nakade, Dhananjay; Mehta, Jitendra; Shahane, Pawan; Gupta, Shitiz; Bhajipale, Sanjay (International Journal of Research in Medical Sciences, 2017)
Background: Extensive soft tissue defects of leg, ankle and foot are challenge to reconstructive surgeons due to lack of local tissue. Microvascular flap coverage has become a standard line of treatment as large amount of tissue transfer is required. Large transverse fasciocutaneous cross leg flap remains an alternative for reconstruction of such extensive defects. We present our experience with this flap in 14 patients. Methods: A total of 14 patients were operated for large transverse fasciocutaneous cross leg flap cover for defects over leg (9), ankle and foot (3) and sole (2). Age group ranged from 4 years to 50 years with 4 patients below 12 years of age. Male to female ratio was 5:2. Flaps were divided at 3weeks and final inset was done. Results: 11 patients had complete flap survival. Two patients had marginal necrosis and one patient had superficial necrosis of proximal flap margin after flap division. One patient with partial skin graft loss at donor area required secondary skin grafting at the time of flap division. Average hospital stay was 34.5 days (range 10 - 50 days). The donor limb had no joint stiffness related to immobilisation and cosmetic outcome of flap and donor area was satisfactory. Conclusions: large transverse fasciocutaneous cross leg flap is safe, technically easy and is associated with minimal donor site morbidity. It offers the possibility of limb salvage in difficult situations.